FRI0058 Comorbidity Indexes/Scales in Rheumatoid Arthritis: A Systematic Literature Review. (10th June 2014) - Martínez-Lόpez, J.A.; Loza, E.; Ortiz, A.; Toledano, E.; Villaverde, V.; Lajas, C.; Castañeda, S.
Abstract : Background: In rheumatoid arthritis (RA), comorbidity might delay diagnosis and influence treatment decisions; it alters survival, outcomes and confounds analysis. Therefore, it is vital to measure it properly. The use of comorbidity indexes/scales could help in daily practice. Objectives: To examine validity, reliability and feasibility of comorbidity indexes in daily practice in RA. Methods: A systematic literature review was performed by 2 reviewers, a librarian and a methodologist. Studies were identified by sensitive search strategies in the main bibliographic databases (Medline, Embase and Cochrane Library) up to May 2013. Mesh terms and text word were used. We selected articles that analyzed comorbidity indexes/scales. Any type of study except case series or case reports was eligible. Two reviewers (JAML and EL) screened the titles and abstracts of the retrieved articles independently. JAML reviewed the selected articles in detail and collected the data from the studies included by using ad hoc standard forms. A hand search was completed by reviewing the references of the included studies. Validity process was evaluated, and study quality using the Newcastle-Ottawa scale. The level of evidence for each comorbidity index/scale was graded with the Oxford Centre for Evidence-based Medicine Levels of Evidence. Results: We included 33 studies (moderate quality, 2 were systematic reviews) that described more than 40 comorbidity indexes, 1 specific for RA. We found a great variability regarding to type of measure of comorbidity, validation populations, number of items included, definitions, scoring method, etc. Content and face validity varied but tended to be high. Reliability was in general moderate-high, but feasibility in daily practice complicated mainly because of lack of time. The table summarizes the characteristics of some of the most popular comorbidity indexes. Conclusions: There is not enough evidence to recommend an especific comorbidity index in RA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5773